Imaging Markers of Subcortical Vascular Dementia in Patients With Multiple-Lobar Cerebral Microbleeds - Lin, Chia-Yen; Jhan, Song-Ru; Lee, Wei-Ju; Chen, Po-Lin; Chen, Jun-Peng; Chen, Hung-Chieh; Chen, Ting-Bin (Frontiers in Neurology, 2021)
Background and Purpose: Small vessel disease (SVD) imaging markers are related to ischemic and hemorrhage stroke and to cognitive dysfunction. This study aimed to clarify the relationship between SVD imaging markers and subcortical vascular dementia in severe SVD burden. Methods: A total of 57 subjects with multiple-lobar cerebral microbleeds CMBs and four established SVD imaging markers were enrolled from the dementia and stroke registries of a single center. Visual rating scales used to semi-quantify SVD imaging changes were analyzed individually and compositely to make correlations with cognitive domains and subcortical vascular dementia. Results: Dementia group had higher subcortical and total white mater hyperintensities (WMHs) and SVD composite scores than non-dementia group. Individual imaging markers correlated differently with one another and had distinct cognitive correlations. After adjusting for demographic factors, multivariate logistic regression indicated associations of subcortical WMHs (OR 2.03, CI 1.24–3.32), total WMHs (OR 1.43, CI 1.09–1.89), lacunes (OR 1.18, CI 1.02–1.35), cerebral amyloid angiopathy-SVD scores (OR 2.33, CI 1.01–5.40), C1 scores (imaging composite scores of CMB and WMH) (OR 1.41, CI 1.09–1.83), and C2 scores (imaging composite scores of CMB, WMH, perivascular space, and lacune) (OR 1.38, CI 1.08–1.76) with dementia. Conclusion: SVD imaging markers might have differing associations with cognitive domains and dementia. They may provide valuable complementary information in support of personalized treatment planning against cognitive impairment, particularly in patients with a heavy SVD load.